Secukinumab is Superior to Ustekinumab in Clearing Skin in Patients with Moderate to Severe Plaque Psoriasis (16-Week CLARITY Results) - Jerry Bagel; John Nia; Peter W. Hashim; Manmath Patekar; Ana de Vera; Sophie Hugot; Kuan Sheng; Summer Xia; Isabelle Gilloteau; Elisa Muscianisi; Andrew Blauvelt; Mark Lebwohl (Adis, Springer Healthcare, 2018)
Abstract Introduction Secukinumab, a fully human anti-interleukin-17A monoclonal antibody, has demonstrated superior efficacy to ustekinumab in the phase 3b CLEAR study of moderate to severe plaque psoriasis. Here, we report 16-week results from CLARITY, a second head-to-head trial comparing secukinumab with ustekinumab. Methods In the phase 3b CLARITY study, patients were randomized 1:1 to receive subcutaneous secukinumab 300 mg or ustekinumab per label. The co-primary objectives were to demonstrate the superiority of secukinumab over ustekinumab at Week 12 in relation to the proportion of patients with (1) 90% or more improvement from baseline Psoriasis Area and Severity Index (PASI 90) and (2) a score of 0/1 (clear/almost clear) on the modified Investigator's Global Assessment (IGA mod 2011 0/1). Key secondary objectives were also assessed, as was Dermatology Life Quality Index (DLQI) 0/1 (no impact of skin disease on patients' quality of life) response. Missing values were handled by multiple imputation except for DLQI 0/1, where last observation carried forward techniques were utilized. Results Both co-primary objectives were met: secukinumab was superior to ustekinumab for the proportion of patients achieving a PASI 90 (66.5% vs. 47.9%) and IGA mod 2011 0/1 response (72.3% vs. 55.4%) at Week 12 (p < 0.0001). PASI 90 responses were greater with secukinumab compared to ustekinumab from as early as Week 4 (16.7% vs. 4.0%) and out to Week 16 (76.6% vs. 54.2%). Similarly, IGA mod 2011 0/1 findings were greater with secukinumab at Week 4 (26.9% vs. 7.8%) and at Week 16 (78.6% vs. 59.1%). DLQI 0/1 response rates were also greater with secukinumab compared to ustekinumab at Week 4 (33.9% vs. 18.0%), Week 12 (64.0% vs. 51.7%), and Week 16 (68.4% vs. 55.9%). Conclusion The results of this study confirm the superior efficacy of secukinumab over ustekinumab in treating patients with moderate to severe psoriasis. Trial Registration Clinicaltrials.gov Identifier, NCT02826603. Funding Novartis Pharma AG, Basel, Switzerland.